Performance of Islamic and conventional banking in Malaysia : a comparative analysis. - Kamsinah Sadar. (2008)
This paper aims to identify if any significant differences exist in bank performance when conventional and Islamic banking operations are compared in a Malaysian setting over the period 1998-2002. The sample in our study consists of the commercial banks and finance companies. To measure and compare the performance, financial ratio analysis is used.